2015
DOI: 10.11138/mltj/2015.5.3.214
|View full text |Cite
|
Sign up to set email alerts
|

Groin pain syndrome: an association of different pathologies and a case presentation

Abstract: Mini review- Case report (Level V).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 67 publications
1
7
0
8
Order By: Relevance
“…In case of suspected presence of IH and ICPWW the gold standard imaging is represented by dynamic US 14 which shows a very high PPV [14][15][16][17] . This study has confirmed the multifactorial aetiology of GPS, and the overlapping of several clinical frameworks which is a common characteris-tic of LSGPS 3,4,19 . For this reason a standard MRI protocol can provide some important information concerning potential clinical entities correlated with the presence of IH and ICPWW.…”
Section: Limitationssupporting
confidence: 76%
See 4 more Smart Citations
“…In case of suspected presence of IH and ICPWW the gold standard imaging is represented by dynamic US 14 which shows a very high PPV [14][15][16][17] . This study has confirmed the multifactorial aetiology of GPS, and the overlapping of several clinical frameworks which is a common characteris-tic of LSGPS 3,4,19 . For this reason a standard MRI protocol can provide some important information concerning potential clinical entities correlated with the presence of IH and ICPWW.…”
Section: Limitationssupporting
confidence: 76%
“…Such long symptoms duration allows us to classify the GPS framework as "long standing GPS" (LSGPS or chronic GPS) in according with Groin Pain Syndrome Italian Consensus Conference on terminology, clinical evaluation and imaging assessment in groin pain in athlete 3 . In a LSGPS, the clinical framework is frequently based on the association of an inguinal pathology and a pubic osteitis (PO) 3,4,19 . It is important to remember that a PO framework is strongly associated with a chronic ALT 29,40 .…”
Section: Mri Findings Alt (Adductor Longus Tendinopathy)mentioning
confidence: 99%
See 3 more Smart Citations